Efeito da telereabilitação nos distúrbios do sono em crianças e adolescentes obesos durante a pandemia de COVID-19: um ensaio clinico quase experimental com acompanhamento - Luiz, Josiane Germano (2022)
AIM: To evaluate the effects of telerehabilitation on sleep disorders in obese children and adolescents. METHODS: Quasi-experimental trial with follow-up, in which 11 obese individuals aged between 6 and 17 years participated, who were evaluated before and after Telerehabilitation with High Intensity Functional Training (HIFT), for 8 weeks, 3 times a week. At home. All were assessed by type IV polysomnography, risk for obstructive sleep apnea, sleep quality and signs of daytime sleepiness, with follow-up after 16 weeks. Results: Regarding type 4 polysomnography data, there was a significant difference-intervention in the percentage of Sleep Efficiency 85(75-85), better sleep quality according to the Post Pittsburgh Sleep Quality Index with p<0.007, and in terms of activity level there was a significant difference x2(3) = 6.04; p<0.05, no level of physical activity after follow-up compared to pre telerehabilitation. Conclusion: This is a preliminary study that confirms the feasibility of telerehabilitation and its beneficial effects for 8 weeks on the quality and efficiency of sleep, altered in obese children and adolescents during the Covid-19 pandemic, and it can be seen, after follow-up for 16 weeks, an improvement in the level of physical activity of these subjects.